2014
DOI: 10.1155/2014/120607
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Cardiac Arrest following K2 Abuse

Abstract: Sudden cardiac death (SCD) accounts for up to 450,000 deaths every year in the United States (Zipes et al. (2006)). Most cases of sudden cardiac death occur in subjects with no prior history of heart disease (Myerburg et al. (1998)). The incidence of sudden death in a general population has been shown to increase contemporaneously with substance abuse (Phillips et al. (1999)). The causative association of sudden death with cocaine, methadone, and volatile agents is well established (Adgey et al. (1995) and Isn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 10 publications
(10 reference statements)
2
49
0
3
Order By: Relevance
“…Son yıllarda, sentetik katyonlar, SK'ler ve ateş çiçeği gibi uyuşturucu ilaçların kötüye kullanımında artış görülmektedir (6). Özellikle SK kullanımı adelosanlar ve genç erişkinler arasında artış göstermektedir (7). Yapılan bir çalışmada, markadan markaya ve seriden seriye değişen farklı kombinasyon ve oranlarda 11 farklı SK saptanmıştır.…”
unclassified
“…Son yıllarda, sentetik katyonlar, SK'ler ve ateş çiçeği gibi uyuşturucu ilaçların kötüye kullanımında artış görülmektedir (6). Özellikle SK kullanımı adelosanlar ve genç erişkinler arasında artış göstermektedir (7). Yapılan bir çalışmada, markadan markaya ve seriden seriye değişen farklı kombinasyon ve oranlarda 11 farklı SK saptanmıştır.…”
unclassified
“…Similar to our cases, Hermanns-Clausen et al (12) reported tachycardia and bradycardia in 18 of 29 patients. Prolonged QT interval was found in the patient reported by İbrahim et al (10). "Bonzai" may lead to very different clinical pictures in terms of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 87%
“…Mckeever et al (9) reported that they found normal coronary arteries on angiography in a 16-year old patients who was investigated because of suspicious myocardial infaction following use of synthetic cannabinoid. In two adult case presentations, myocardial infaction and sudden cardiac arrest following use of substance were reported in two patients who had known coronary artery disease (10). Although chest pain related with myocaridal ischemia is frequent in the adulthood, it is observed rarely in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…7 Activation of glutamate receptors and GABA channel blockade may also be responsible for anxiety due to SC use. 8 Agitation and violent behavior, suicidal and homicidal ideations in addition to self-injurious behaviors have been reported in case studies. 9 The implications of acute SC use on human health remains poorly understood and less is known about the long term effects of these drugs.…”
Section: Adverse Effectsmentioning
confidence: 99%